Integrated Bali Cattle Development Model Under Oil Palm Plantation - Matondang, Rasali Hakim; Talib, C (Indonesian Animal Sciences Society, 2015)
Bali cattle have several advantages such as high fertility and carcass percentage, easy adaptation to the new environment as well. Bali cattle productivity has not been optimal yet. This is due to one of the limitation of feed resources, decreasing of grazing and agricultural land. The aim of this paper is to describe Bali cattle development integrated with oil palm plantations, which is expected to improve productivity and increase Bali cattle population. This integration model is carried out by raising Bali cattle under oil palm plantation through nucleus estate scheme model or individual farmers estates business. Some of Bali cattle raising systems have been applied in the integration of palm plantation-Bali cattle. One of the intensive systems can increase daily weight gain of 0.8 kg/head, calfcrop of 35% per year and has the potency for industrial development of feed and organic fertilizer. In the semi-intensive system, it can improve the production of oil palm fruit bunches (PFB) more than 10%, increase harvested-crop area to 15 ha/farmer and reduce the amount of inorganic fertilizer. The extensive system can produce calfcrop ³70%, improve ³30% of PFB, increase business scale ³13 cows/farmer and reduce weeding costs ³16%. Integrated Bali cattle development may provide positive added value for both, palm oil business and cattle business. Key words: Model, integration, Bali cattle, oil palm plantations